SUBSEQUENT INJURY DURING INJURY RECOVERY IN ELITE ATHLETICS: COHORT STUDY IN SWEDISH MALE AND FEMALE ATHLETES. Issue 7 (11th March 2014) - Jacobsson, J; Timpka, T; Kowalski, J; Ekberg, J; Nilsson, S; Dahlström, Ö; Renström, P
Abstract : Background: In elite athletics, epidemiological studies covering cross-discipline populations of athletes have reported a heavy burden of injuries related to overuse. Many athletes continue to expose themselves to extensive training and competition loads while suffering from partial time loss injuries (forcing them to change their practice schedules). Objective: To examine risk indicators associated with sustaining a secondary (subsequent) injury while recovering from a primary (index) injury. Design: Prospective epidemiological study using web-based data collection. Setting: Swedish elite youth (U17) and adult athletics athletes. Data were collected between March 2009 and March 2010. Participants: 292 youth and adult athletes (91%) responded regularly to web-based questionnaires from an eligible study population of 321 athletes. Risk factor assessment: Athlete's sex, age, event group and training load. Main outcome measures: Secondary new injury during recovery from a primary (index) injury. Results: A total of 122 (42 %) of the athletes reported more than one injury during the study period. Multiple Cox proportional hazards regression analyses revealed risk differences with regard to event group (P=.006) and training load (P=.047) for athletes who sustained a secondary new injury during recovery from a first injury; athletes in the combined events group (hazard ratio (HR) 4.14; 95% CI 1.82–9.40) had almost a fourfold increased risk compared to jumpers and throwers and athletes in the third TLRI quartile (HR=2.02; 95% CI 1.29–3.63) a twofold risk for sustaining a secondary injury compared with their peers. Conclusions: The risk for sustaining a new secondary injury while recovering from a primary injury is high among athletics athletes. Competing in combined events and a high score in the training load index (combining hours and intensity) are associated with particularly increased risk. Further studies measuring training content during the rehabilitation period and development of protocols for safe return to athletics are warranted.